Peatland Vascular Plant Leaf N Concentrations (10 Species) From Leaves Collected From N-Addition Plots in an Alberta Peatland, 2011-2015 - R Kelman Wieder; Dale H Vitt; Melanie A Vile; Jeremy A Graham; Jeremy A Hartsock; Hope Fillingim; Melissa House; James C Quinn; Kimberli D Scott; Meaghan Petix; Kelly J McMillen (Environmental Data Initiative, 2019)
Development of the oil sands has led to increasing atmospheric N deposition, with values as high as 17 kg N ha -1 yr -1 ; regional background levels <2 kg N ha -1 yr -1 . Bogs, being ombrotrophic, may be especially susceptible to increasing N deposition. To examine responses to N deposition, over five years, we experimentally applied N (as NH 4 NO 3 ) to a bog near Mariana Lakes, Alberta, at rates of 0, 5, 10, 15, 20, and 25 kg N ha -1 yr -1 , plus controls (no water or N addition). In July of each year, we collected new growth of ten species of vascular plants, returned them to the lab, cleaned them, dried and ground them, and ran them on a Flash EA 1112 Series CN Soil Analyzer. Leaf N concentration responses to increasing N input differed between species. Increasing N input led to increasing leaf N concentrations in A. polifolia , C. calyculata , V. vitis-idaea , and V. oxycoccos , with differences in N concentrations between years for all of these species except V. vitis-idaea . There was no leaf N concentration response to increasing N input for E. vaginatum , R. chamaemorus , S. trifolia , or K. polifolia . Water input alone had no significant effect on leaf N concentration for any of the species (p >= 0.18). Although aboveground growth of bog vascular plants may be a general response to increasing N deposition, we do not have a species-specific mechanistic understanding of how growth and leaf/needle N concentrations respond to increasing N deposition, however, there appeared to be no strong evidence for luxury consumption of N.